The Influence of Bank Environmental Performance and Sustainability Committee on Bank Financial Performance through Green Banking - Ni Luh Betty Oktarini; Lukman Effendy (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to analyze the influence of banks' environmental performance and the existence of sustainability committees on banks' financial performance through green banking in banks that implement green banking in Indonesia and are listed on the Indonesia Stock Exchange (IDX) from 2018-2022. The sampling technique used is purposive sampling with specific criteria, resulting in 65 data samples from 13 banks that meet these criteria. This study employs path analysis to determine the effect of independent variables on dependent variables and the Sobel test to determine the indirect effect of the mediating variable on both the dependent and independent variables, using Eviews 12 software. The results indicate that the variable Banks' Environmental Performance affects Green Banking, while the variable Sustainability Committees do not significantly affect Green Banking. Green banking influences banks' financial performance, and it cannot mediate the effect of environmental performance on banks' financial performance. Additionally, Green Banking cannot mediate the impact of Banks' Sustainability Committees on Banks' Financial Performance.